Beyond the crisis: what is the future for small business? Challenges, opportunities and lessons learned: Proceedings 5th PISB Worksho, Urbino 3-4 December 2021 (Piccola Impresa / Small Business, 2021)
Dear readers, in this volume, we are pleased to present the proceedings of the 5th Workshop organised by the journal Piccola Impresa/Small Business in collaboration with the Association for the study of small enterprises (ASPI), the Research Center on Entrepreneurship and Small-medium firms (CRIMPI), the Italian Academy of Business Economics (AIDEA) and the European Council for Small Business and Entrepreneurship (ECSB). The workshop title was “Beyond the crisis: what is the future for small businesses? Challenges, opportunities and lessons learned”, and it took place online on December 4-5, 2021.